UMPSA achieves dual success at Huawei ICT Competition Malaysia 2024–2025 - Hoh, Wei Siang (UMPSA, 2024)
PUTRAJAYA, 3 December 2024 - Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) proudly celebrates its outstanding achievement at the Huawei ICT Competition Malaysia 2024–2025 National Finals.